Studi tentang jenis penelitian skripsi mahasiswa ilmu keolahragaan yang berkategori analisis gerak - Elok Sudibyo, (Ilmu Keolahragaan, 2012)
Abstract: This stuy aima to determine the types of research in sports science students S1 theses (in this case the students are expected to hold a sports degree), especially to determine the percentage of students S1 thesis which are categorized as  motion analysis. The data in this research were obtained through the study of documentation, by analyzing the students S1 thesis which is documented in the library of S1 Sport Science study program. The study was conducted in December 2011. There are 219 S1 thesis titles obtained in the library. The result of study shows that the types of students S1 thesis has been done can be categorized as follows: 22,83% (correlation), 30,14% (contribution), 14,16% (quasi experiment), 8.22% (study of comparative), 10,05% (survey), 5.02% (motion analysis), and the remaining 9.59% (profiles, the game statistics, development of instruments, etc.). Based on the classification is shown that the students thesis which are categorized as motion analysis is still very low, that percentage is only 5,02%